2022
DOI: 10.2217/pgs-2021-0144
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Study of Anthracycline-Induced Cardiotoxicity in Mexican Pediatric Patients

Abstract: Background: The aim of this study was to evaluate the association between well-defined genetic risk variants in SLC28A3, RARG and UGT1A6 and anthracycline-induced cardiotoxicity in Mexican pediatric patients. Methods: We tested a cohort of 79 children treated with anthracyclines for the presence of SLC28A3-rs7853758, RARG-rs2229774 and UGT1A6-rs17863783. Results: The SLC28A3-rs7853758 variant was more frequent in this cohort, while the UGT1A6-rs17863783 and RARG-rs2229774 variants were present at lower frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
7
1
3
Order By: Relevance
“…Specifically, the synonymous variant rs7853758, located in exon 14, is the most extensively studied AIC polymorphism in SLC28A3 , for which the minor allele has a protective effect in paediatric patients. This variant has been consistently associated AIC resistance, as discovered and replicated by Visscher et al 32,33 Similarly, this finding was also confirmed in another independent cohort of Mexican children 56 . Furthermore, Siemens et al found that the rs7853758 variant imparted more significant protection for patients receiving higher anthracycline doses, and carriers of this variant may be able to safely tolerate increased doses of anthracyclines 57 .…”
Section: The Current State Of the Pharmacogenetics Of Transmembrane T...mentioning
confidence: 71%
See 1 more Smart Citation
“…Specifically, the synonymous variant rs7853758, located in exon 14, is the most extensively studied AIC polymorphism in SLC28A3 , for which the minor allele has a protective effect in paediatric patients. This variant has been consistently associated AIC resistance, as discovered and replicated by Visscher et al 32,33 Similarly, this finding was also confirmed in another independent cohort of Mexican children 56 . Furthermore, Siemens et al found that the rs7853758 variant imparted more significant protection for patients receiving higher anthracycline doses, and carriers of this variant may be able to safely tolerate increased doses of anthracyclines 57 .…”
Section: The Current State Of the Pharmacogenetics Of Transmembrane T...mentioning
confidence: 71%
“…This variant has been consistently associated AIC resistance, as discovered and replicated by Visscher et al 32,33 Similarly, this finding was also confirmed in another independent cohort of Mexican children. 56 Furthermore, Siemens et al found that the rs7853758 variant imparted more significant protection for patients receiving higher anthracycline doses, and carriers of this variant may be able to safely tolerate increased doses of anthracyclines. 57 Carriers of the rs7853758 minor allele exhibit reduced SLC28A3 mRNA expression levels in monocytes compared with the wild-type allele, 58 and the altered expression of SLC28A3 was furthermore reported to influence the severity of AIC in patientderived human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs).…”
Section: Influx Transporters: Slc Familymentioning
confidence: 99%
“…In this study we could not verify clinical risk factors to be significant risk factors for developing DIC, of which previous studies have identified hypertension, female sex, age, cumulative anthracycline dose, as risk factors for DIC 3,14,27 . It may be possible that the small sample size in our study could have reduced the statistical power to demonstrate the significance of association of the clinical risk factors with DIC 12,[28][29][30][31][32][33] If we considered doxorubicin cumulative dose, we observe that there was no clear association between cumulative doxorubicin dose and cardiotoxicity (p = 0.357), which is not as expected 11,12,18,[34][35][36][37][38] . However, the high frequency (60.7%) of the cardioprotective variant could have influenced this dose relationship in our study.…”
Section: Discussionmentioning
confidence: 84%
“…We did not find any, and we hypothesized that these AEs do not occur frequently in our population. In Mexico, in most protocols that include anthracycline treatment, the cumulative dose is lower than 300 mg/m 2 [30]. In addition, dexrazoxane, an iron chelator, reduces early myocardial injury during anthracycline treatment [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, in most protocols that include anthracycline treatment, the cumulative dose is lower than 300 mg/m 2 [30]. In addition, dexrazoxane, an iron chelator, reduces early myocardial injury during anthracycline treatment [30,31]. However, approximately 57% of CCSs may present asymptomatic signs of cardiotoxicity up to 6.2 years after anthracycline treatment completion [13].…”
Section: Discussionmentioning
confidence: 99%